Geoarchaeological survey in the Wādī al-Kabīr basin, Wilāyāt Ibrī, Oman: a preliminary report (poster) - Kondo, Yasuhisa; Beuzen-Waller, Tara; Miki, Takehiro; Noguchi, Atsushi; Desruelles, Stéphane; Fouache, Éric (Proceedings of the Seminar for Arabian Studies, 2014)
This paper reports on the geoarchaeological survey in the Wādī al-Kabīr basin, located in the southern piedmont of the al-Hajar mountains, to the north-east of Ibrī, Oman. The goal of the survey was to understand the spatial patterns of human occupation of the region during the Late Pleistocene and Holocene, paying special attention to the development of landscape and topography. The survey comprised archaeological and geomorphological explorations. Both approaches employed satellite remote sensing and GIS-based mapping of surface features. From the geomorphological viewpoint, the survey area was an alluvial plain washed and surrounded by two major wadis — Wādī al-Kabīr and Wādī Khuwaybah. In this area, the archaeological team documented twenty-three sites and scatters. Middle to Late Palaeolithic artefacts were identified in the piedmont areas, while Holocene lithics, characterized by Fasad points, end-scrapers, and drills, were scattered on residual hills and terraces. The team identified a total of 246 cairns, most of which look like Hafit-type tombs. Some of the cairns were associated with lithic concentration. There was a Bronze Age and Islamic settlement on the terrace between the two wadis. At that site, called al-Hāsī, the team mapped at least five Bronze Age towers, two Umm an-Nar type graves, enclosure walls, irrigation channels with an aqueduct bridge, bunds to prevent floods, and traces of crop field boundaries and buildings. The results of systematic surface collection and soil sampling in the northern sector suggested that a Bronze Age settlement is probably present underneath the crop fields of the Islamic period.